Binderless particleboards obtained 100% from winery by-products for the packaging industry - Fernandes, Raquel A.; Lopes, Sandro; Ferreira, Nuno; Santos, Jorge; Martins, Jorge M.; Carvalho, Luisa H. (Frontiers in Food Science and Technology, 2024)
The valorization of bioeconomy by-products holds immense significance in achieving sustainability goals and fostering resource efficiency, not only to reduce the amount of waste generated but also to significantly decrease the carbon footprint associated with several industrial fields, by promoting circular economy. The wine industry is not only one of the major contributors for world’s economy but also a great producer of by-products, with no valorization process associated. Grape stalks are a great source of chemical molecules, as polyphenols, that can be applied in the production of bio-adhesives. In the present work, grape stalk particles were used as raw material to obtain a highly rich extract with bonding properties through solid/liquid extraction. Different extraction agents were tested (water, NaOH, and Na2CO3) at varied concentrations (0.1%, 0.5%, and 1.0%, respectively). Additionally, extracts were chemically characterized, and the bonding capacity was also evaluated. Using NaOH 1.0%, an extraction efficiency of 8.9% and a total content of polyphenols of 1.4% were achieved. Moreover, all extracts presented an interesting bonding capacity (>1.0 MPa) by hot-press at 120°C for 120 s. The composite panel produced using grape stalk adhesive and vine strain particles fulfills the requirements for type P1 particleboards in terms of internal bond strength, reaching 0.66 MPa. The mechanical and wettability properties of composite material allow foreseeing a promising application in the food packaging industry.